2015
DOI: 10.2298/bah1503365v
|View full text |Cite
|
Sign up to set email alerts
|

Research on subclinical mastitis and its ethiology in different breeds of cows

Abstract: Detection of subclinical mastitis in five different breeds of cows were done on the territory of a municipality Kljuc, through all four year seasons by using the California mastitis test, at the level of the udder?s quarter with a certificate of bacteriological findings in order to justify their application in the diagnosis of mastitis. In total, 2150 cows of different breed composition: Simmental 1090, red Holstein 322, Holstein-Friesian 340, montafon 108 and various crossbreeds of 290 in to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
0
3
Order By: Relevance
“…He found 35 percent prevalence of subclinical mastitis. However, Varatanovic et al, (2015) tested 1978 cows from total of 2150 cows by CMT and observed 56.02% (1108 cows) prevalence which was lower than the result of present study. The prevalence of subclinical mastitis in present study was lower than reported by Kurjogi and Kaliwal (2014).…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…He found 35 percent prevalence of subclinical mastitis. However, Varatanovic et al, (2015) tested 1978 cows from total of 2150 cows by CMT and observed 56.02% (1108 cows) prevalence which was lower than the result of present study. The prevalence of subclinical mastitis in present study was lower than reported by Kurjogi and Kaliwal (2014).…”
Section: Resultscontrasting
confidence: 93%
“…However, Varatanovic et al, (2015) concluded that CMT represents important diagnostic method in detection of subclinical mastitis in cows and out of 4432 quarters 2166 (48.87%) were found positive to CMT which was higher than the result of present study. According to Bhutto et al, (2012), 507 (53%) quarters out of 960 quarters reported as negative while 192 (20%), 146 (15%), 64 (7%) and 51(5%) quarters as positive for subclinical mastitis detected by CMT.…”
Section: Resultscontrasting
confidence: 84%
“…He found that the prevalence of subclinical mastitis in dairy cows was 35%. Varatanovic et al, (2015) and Bonde et al, (2014) reported that 60.00% and 56.02% the prevalence of subclinical mastitis in dairy cows respectively which was higher that of result of present investigation.…”
Section: Resultscontrasting
confidence: 68%